What influences patients' willingness to choose in online health consultation? An empirical study with PLS–SEM. Issue 12 (19th August 2020) - Wan, Yan; Zhang, Yifan; Yan, Mengling
Abstract : Purpose: Online trust is a key factor for successful online transactions. To some extent, online health consultation can be considered an online transaction. Owing to the unique physician–patient relationship, patients' choice of physicians within an online health consultation setting may not only be based on rational judgments but also considerably affected by their feelings. Hence, the purpose of this study was to explore which physicians' attributes affect patients' cognitive and affective trust in physicians, as well as how these two variables and their association affect patients' willingness to choose. Design/methodology/approach: Based on the broad conceptual framework of online trust, this paper proposed a set of hypotheses that were tested through analyzing survey data using structural equation modeling techniques. Findings: Results showed that physicians' ability had a significant positive influence on patients' cognitive trust in the physician; physicians' integrity and benevolence had a significant positive influence on patients' affective trust in the physician; cognitive and affective trust had a significant positive impact on patients' willingness to choose and there were significant positive interactions between affective and cognitive trust. Originality/value: This study theoretically enriches the generic model of online trust. From the practical perspective, it will provide physicians working in online health consultation platforms and relevant practitioners with baseline information on the topic and advice for decision-making toward service enhancement and clientele improvements.